Front Cover: New Approaches for Absolute Quantification of Stable‐Isotope‐Labeled Peptide Standards for Targeted Proteomics Based on a UV Active Tag. Issue 10 (27th May 2020) - Schnatbaum, Karsten; Solis‐Mezarino, Victor; Pokrovsky, Daniil; Schäfer, Frederike; Nagl, Dennis; Hornberger, Lars; Zerweck, Johannes; Knaute, Tobias; Avramova‐Nehmer, Julia; Schutkowski, Mike; Hornung, Veit; Wenschuh, Holger; et al.
Abstract : DOI: 10.1002/pmic.202000007 Targeted proteomics, a powerful strategy for simultaneous determination of human proteins, requires quantified stable isotope labeled (SIL) peptide standards to enable precise protein quantification. In article number 2000007 by Karsten Schnatbaum et al., a new approach for absolute quantification of SIL peptides is reported, which eliminates the need for laborious and expensive amino acid analysis based protocols. The method relies on a UV‐active quantification tag (Qtag) that is removed by tryptic digestion and was exemplarily applied for accurate quantification of the in‐vivo specificity of a histone methyltransferase.